Ethical considerations about the use of metotrexate in ectopic pregnancy (TP) - Casas M., María de la Luz; Sánchez Javier, Rosa María (Acta Bioethica, 2012)
Ectopic pregnancy (EP) consists in the implantation of a fertilized ovule in the fallopian tube. The fact is that EP will continue to appear many times to physicians in the form of an urgent clinical episode of intra abdominal bleeding. The physician may consider then as certain the death of the embryo and he/she will intervene to extirpate the embryo remains and the bleeding and perforated fallopian tube. In this way he/she will revert the serious immediate threat to the life of the mother. The medical treatment with metotrexate (MTX) is a safe and effective procedure in the treatment of ectopic pregnancy, without the potential risks of surgery. The act of the physician will never be to attempt directly against the embryo, but on the cause of the pathology, that may provoke the death of the embryo. The medical intervention in these cases has been considered by some as a type of indirect abortion and, therefore, an act contrary to ethics, considering the invulnerability of human life. But the ethical argumentation about the objective of this intervention may be posed under the principle of double effect.